Facile Synthesis of [6,6]-Phenyl-C61/71-Butyric Acid Methyl Esters via Sulfur Ylides for Bulk-Heterojunction Solar Cell - Ito, Takatoshi; Iwai, Toshiyuki; Matsumoto, Fukashi; Hida, Koichi; Moriwaki, Kazuyuki; Takao, Yuko; Mizuno, Takumi; Ohno, Toshinobu (Synlett, 2013)
A one-step, mild synthesis of methanofullerenes as electron acceptors for solution-processed bulk-heterojunction solar cells was developed. [6,6]-Phenyl-C61-butyric acid methyl ester {[60]PCBM} was directly synthesized in good yields, by the reaction of fullerene with sulfur ylide derivatives in the presence of 1,8-diazabicyclo-[5.4.0]undec-7-ene (DBU) at room temperature. This method was also successfully applied to the preparation of [6,6]-phenyl-C71-butyric acid methyl ester {[70]PCBM}.
Keywords: methanofullerene; PCBM; photovoltaics; sulfur ylide; addition–elimination reaction